The effectiveness of the hemoglobin, albumin, lymphocyte, and platelet (HALP) score in predicting lymph node metastasis in radiologically n0 locally advanced upper rectal cancer - Bardakçı, Osman; Çetinkaya, Gökay (Frontiers in Oncology, 2025)
Background and ObjectiveReliable preoperative identification of lymph node metastasis in clinically node-negative (cN0) patients with locally advanced upper rectal cancer (LAURC) remains a major clinical challenge due to the limited sensitivity of imaging modalities. The HALP score—calculated from hemoglobin, albumin, lymphocyte, and platelet counts—has emerged as a promising marker reflecting systemic inflammation and nutritional status. This study aimed to investigate the association between preoperative HALP scores and histopathologically confirmed lymph node metastasis in cN0 LAURC patients and to assess its diagnostic performance.MethodsThis retrospective study included 62 patients who underwent curative resection for cN0 LAURC between January 2020 and December 2023. HALP scores were computed using the formula: hemoglobin (g/L) × albumin (g/L) × lymphocyte count (/L) ÷ platelet count (/L), based on fasting blood samples collected within one week prior to surgery. Patients were stratified according to the presence or absence of pathological lymph node metastasis. ROC curve analysis was used to determine the optimal HALP cut-off value. Strict exclusion criteria were applied to minimize confounding from comorbidities affecting hematologic parameters.ResultsLymph node metastasis was confirmed in 21 patients (33.9%). Patients with metastasis had significantly lower HALP scores compared to those without (p = 0.007). ROC analysis identified a HALP cut-off value of 6.98, yielding a sensitivity of 73% and specificity of 81% (AUC = 0.695; 95% CI: 0.56–0.83; p = 0.013). No significant associations were observed between HALP score and TNM stage or demographic variables.ConclusionThe HALP score is significantly associated with pathological lymph node metastasis in cN0 LAURC patients and may serve as a simple, inexpensive, and clinically applicable biomarker to support preoperative staging. Further prospective studies with survival-based endpoints are warranted to validate its prognostic value.